Flavonoids of an extract of Pterospartum tridentatum showing endothelial protection against oxidative injury - Vitor, RE (2015)
Pterospartium tridentatum is a Leguminosae that grows spontaneously in Portugal. The flowers are used in popular medicine for the treatment of throat irritation conditions and in herbal mixtures for diabetes. Diabetic vascular complications are due, among